THE CASE OF THE PREFIX INTENSIFICATION IN FRENCH LANGUAGE - Rashidova, Laura (Журнал иностранных языков и лингвистики, 2023)
We would like, with this thesis, to contribute to the stripping of the field of prefix intensification. Indeed, intensification greatly influences our communication, especially since it is essential to attract the attention of our interlocutors. This is why there are many procedures, the prefixation of which interests us here in particular. To sum up, there is indeed research on the subject, which confirms that the prefix does not have to mean repetition, that there is sometimes an added sense of intensity in such a case, and that the context decides which verb must be used when the simple verb and the prefixed verb do not offer any semantic difference.